The validity of general and specific strength tests to predict the Shot Put performance - a pilot study - Reis, V. M.; Ferreira, A. J. (International Journal of Performance Analysis in Sport, 2003)
The aim of the present study was to evaluate the precision of several general and specific strength tests to predict the Shot Put performance. Eleven male Shot Putters performed a battery of seven tests on the early and on the peak phase of a competitive season. A significant improvement was observed during the season on the Shot Put performance as well as on the tests performance. The jumping tests did not correlate with the Shot Put performance. The throwing tests and the heavy-lift tests have shown significant associations with the Shot Put performance. These associations were stronger on the peak-phase of the season. Therefore, the adoption of these tests for assessment purposes may lack the proper validity when they are performed during a preparation phase or during the early competitive season. The results suggest that a combination of throwing tests (Over-Head Back Throw and Squat Double-Jump Front Throw) and heavy-lift tests (Bench Press, Half Squat and Power Snatch) may provide a good predictive power, as they could explain ~88% of the variance of the Shot Put performance with a relative error of ~2.7%. More studies are warranted with larger samples, in order to confirm the results we have obtained.